Learning Needs of Pharmacists for an Evolving Scope of Practice - Zubin Austin; Paul Gregory (MDPI AG, 2019)
Around the world, changes in scope of practice regulations for pharmacists have been used as a tool to advance practice and promote change. Regulatory change does not automatically trigger practice change; the extent and speed of uptake of new roles and responsibilities has been slower than anticipated. A recent study identified 9 pre-requisites to practice change (the 9Ps of Practice Change). The objective of this study was to describe how educationalists could best apply these 9Ps to the design and delivery of continuing professional development for pharmacists. Twenty community pharmacists participated in semi-structured interviews designed to elicit their learning needs for scope of practice change. Seven supportive educational techniques were identified as being most helpful to promote practice change: (i) a coaching/mentoring approach; (ii) practice-based experiential learning; (iii) a longitudinal approach to instructional design; (iv) active demonstration of how to implement practice change; v) increased focus on soft-skills development; (vi) opportunities for practice/rehearsal of new skills; and (vii) use of a 360-degree feedback model. Further work is required to determine how these techniques can be best applied and implemented to support practice change in pharmacy.